The Determinants of Bank Liquidity: Case of Tunisia - Ben Moussa, Mohamed Aymen (International Journal of Economics and Financial Issues, 2015)
Liquidity is an important variable for the bank and the banking system components. So it is interesting to show its determinants. Thus, we used a sample of 18 banks in Tunisia in for 2000-2010period. We estimated two measures of liquidity (liquid assets / total assets; total loans / total deposits). Through the method of static panel and method of panel dynamic, we found that (financial performance, capital / total assets, operating costs/ total assets, growth rate of GDP, inflation rate, delayed liquidity) have significant impact on bank liquidity while (size, total loans / total assets, financial costs/ total credits, total deposits / total assets) does not have a significant impact on bank liquidity. Keywords: bank; bank liquidity; static panel; Tunisia; dynamic panel JEL Classifications: C5; G2; G21